PERANCANGAN STRATEGI PENGEMBANGAN USAHA BATERAI PACK LITIUM MENGGUNAKAN METODE QUANTITATIVE STRATEGIC PLANNING MATRIX (QSPM) PADA PT XYZ - Savira Henrika Putri (2023)
PT XYZ is a startup company in the automotive business and electric vehicle conversion technology (Electric Vehicle/EV). This company plans to produce lithium batteries for electric vehicles in Indonesia with a lithium battery pack type of 21700 Lithium-Ion Cell Battery. The purpose of this study is to determine the business development strategy that must be carried out based on the evaluation and assessment of the company's internal and external factors. To find out the strategy, the methods used are the IFE matrix, EFE matrix, IE matrix, SPACE matrix, SWOT matrix, and QSPM. Based on the processing of the IE matrix, the company is in cell V with the hold and maintain category and is in the aggressive quadrant of the SPACE matrix. In the SWOT matrix, there are 8 formulations of alternative strategies. At the QSPM stage, the alternative strategy that has the highest Sum Total Attractive Score is the strategy "Increasing sales with the potential of EV market growth" with a value of 6,143.